MICROMYCETES OF CONTAMINATED SOILS AROUND KAJARAN CITY (ARMENIA) (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
In the current research, we investigated soil micromycetes-decomposers around Kajaran City. As a result of the studies, 30 micromycetes were identified as belonging to 16 genera of which 1 belongs to Basidiomycota, 1 – to Mortierellomycota, 3 – to Mucoromycota, and 11 – to Ascomycota. Changes in the species composition and some morphological features of soil fungi are observed depending on the industrial pollution.
Keywords: contaminated territory; soil fungi; micromycetes; dilution method; copper-molybdenum plant